Form Exploration with Gist Method A Case Study of Product Design - Devanny Gumulya; Handoko Sutantio (JURNAL RUPA, 2022)
To be successful in today’s competitive market, businesses must have a clear product recognition among their users. Consumers frequently have a wide range of products to choose from, making it difficult for a company’s products to be discovered and remembered. An important factor is product recognition and how we perceive it through our perception, which is primarily an identification process that is based on familiarity, resemblance, or similarity. Product gist is a technique used by product designers to visually evaluate product forms during the design process. The study employs an exploratory qualitative approach with multiple case studies in three design projects. The findings confirm that the gist method can assist product designers in creating strong product recognition. The gist method assists designers in identifying key representations that can be kept, modified, or eliminated in order to create new product recognition through typological innovation. Keywordsgist method, product design, product recognition